Disseminated Neurocysticercosis With Intraventricular and Cisternal Extension Without Hydrocephalus: A Case Report - Bibek Shrestha; Priyesh Shrestha; Bikram Prasad Gajurel; Grishma Kandel; Laxmi Shah (Clinical Case Reports)
ABSTRACT Neurocysticercosis, a leading cause of acquired epilepsy, can present as disseminated disease with widespread cystic lesions. A 33‐year‐old male with seizures and weakness showed radiologically confirmed neurocysticercosis. Treatment with steroids, antiparasitics, and antiseizure medication led to improvement. Early diagnosis and public health measures are crucial to reducing the burden.